The cognitive and neural bases of human tool use - Cristina Massen (Frontiers Research Topics, 2015)
Humans are not unique in using tools. But human tool use differs from that known to occur in nonhumans in being very frequent, spontaneous, and diversified. So a fundamental issue is, what are the cognitive and neural bases of human tool use? This Research Topic of Frontiers provides a venue for leading researchers in the field of tool use to present original research papers, integrative reviews or theoretical articles that further our understanding of this topic. Articles address a wide range of issues including, for instance, the nature of the underlying representations (e.g., conceptual, sensorimotor), the mechanisms supporting the incorporation of tools into body schema, the link between imitation and tool use, or the evolutionary origins of human tool use. Articles are included from experimental psychology, neuropsychology, neuroimaging, neurophysiology, developmental psychology, ethology, comparative psychology, and ergonomics. The goal of this Research Topic of Frontiers is to provide a state-of-the-art view of the field.